Accountability Analysis of State Civil Apparatus Career Development in Maybrat Regency (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
This study aims to analyze the Accountability of Career Development of State Civil Apparatus in Maybrat Regency. Judging from the aspects of transparency, liability, controllability, responsibility and responsiveness. This research was conducted at the Agency for Personnel and Human Resources Development, Maybrat Regency. The research method used is descriptive qualitative. Data collection techniques using in-depth interviews, observations and documentation studies. While the data analysis techniques used are data condensation, data presentation, verification and drawing conclusions. The results of this study indicate that the Accountability of State Civil Apparatus Career Development in Maybrat Regency in the aspect of Transparency is transparent enough, but in terms of the Liability dimension it has not been fully implemented because there are several obstacles faced by the BKPSDM of Maybrat Regency, and in the Controllability dimension of State Civil Apparatus career development accountability in Maybrat Regency has in accordance with the BKPSDM's main task and responsibility, while in terms of accountability, career development, State Civil Apparatus in Maybrat Regency has followed the applicable rules regarding personnel management, as seen from the BKPSDM, Maybrat Regency, has received an award from BKN, while for the Responsiveness dimension of Accountability of State Civil Apparatus Career Development, Maybrat Regency is seen from the presence of the program includes echelons for DIKLATPIM.